Needs for Primary School Teacher Educators’ Continuing Professional Development Responding to Academic Program Quality Assurance - Huong, Trinh Thi; Hao, Phan Nhat; Vy, Phan Ngoc Tuong (Journal of Ecohumanism, 2025)
Primary education plays a crucial role in shaping the foundation of a child’s academic and personal development, yet less research was conducted for this area, particularly regarding primary teacher training at university level. To fulfill this gap, the current study explored the concerns raised by accreditors regarding the bachelor of education (B.Ed.) program in primary teacher education (PTE) at a university in Vietnam. Using a qualitative case study approach, data were collected through document analysis and structured interviews with five experienced teacher educators. The findings identify key concerns raised by accreditors, including curriculum design, student support, faculty development, and program evaluation. The study further allowed teacher educators to voice their strategies in response to these concerns. The results suggest that effective continuing professional development (CDP) including raising awareness and practices for competency-based education, building structured mentorship with pre-service teachers, and engaging in diverse professional development opportunities. By prioritizing these aspects, teacher educators can better equip themselves to support student learning and address evolving educational challenges, ultimately improving accreditation outcomes and enhancing CPD practices in primary education teacher training programs.